WHO guidelines for severe malnutrition: are they feasible in rural African hospitals?. Issue 3 (2nd May 2006) - Karaolis, Nadina; Jackson, Debra; Ashworth, Ann; Sanders, David; Sogaula, Nonzwakazi; McCoy, David; Chopra, Mickey; Schofield, Claire
Abstract : Aims: To assess the feasibility of implementing and sustaining the WHO guidelines for inpatient management of severe malnutrition in under-resourced rural South African hospitals, and to identify any constraints. Intervention: Three 2-day training workshops were held in 1998, followed by monthly 1-day visits for 5 months, ending in March 1999, in two rural district hospitals with limited resources in Eastern Cape Province, South Africa. Methods: A 12-month observational study was conducted from April 2000 to April 2001 in Mary Theresa and Sipetu hospitals (Eastern Cape Province, South Africa), including 1011 child-hours of observation on the wards, medical record reviews, interviews with carers and staff, and inventories of essential supplies. All admissions (n = 193) for severe malnutrition to the two hospitals were studied. The main outcomes were the extent to which the 10 steps for routine care of severely malnourished children were implemented, proficiency of performance and constraining factors. Results: The hospitals made the changes required in clinical and dietary management, but the tasks were not always performed fully or with sufficient care. Play and stimulation and an effective system of follow-up were not implemented. Doctors' poor knowledge, nurses' inattentiveness and insufficient interaction with carers were constraints to optimal management. The underlying factors were inadequate undergraduate training, understaffing, high doctor turnover and low morale. Conclusions: Guidelines for severe malnutrition are largely feasible but training workshops are insufficient to achieve optimal management as staff turnover and an unsupportive health system erode the gains made and doctors treat cases without having being trained. Medical and nursing curricula in Africa must include treatment of severe malnutrition.